Dielectric and magnetic properties of Nb substituted hexagonal Ba6Y2Ti4O17 (BYTO) perovskite oxides - Yadava S.S.; Singh L.; Ji M.; Kumar A.; Mandal K.D.; Lee Y. (My University, 2025)
In this study, niobium (Nb) substituted barium yttrium titanates, Ba6Y2Ti4−xNbxO17, (BYTNbO, x = 0.0, 0.05, 0.1, and 0.2), were synthesized via semi-wet route at a relatively low sintering temperature. Rietveld refinement of the X-ray diffraction patterns of BYTNbO confirmed that all the compositions have a hexagonal layered perovskite structure with the space group of P63/mmc. Nb5+ substitution at Ti-site in Ba6Y2Ti4O17 (BYTO) induces the formation of magnetically active ion of Ti3+ to enhance the magnetization. Remnant magnetization and magnetic coercivity were increased with decreasing temperature due to the disordered magnetic domains. The magnetization of Ba6Y2Ti3.9Nb0.1O17 also increased to 3.68 × 10−4 emu g−1 by Nb substitution in BYTO. The Curie temperature of x = 0.05, 0.1, and 0.2 were found to be 15.76, 17.77, and 14.12 K, respectively. The dielectric properties of all the compositions were investigated in the frequency range of 100–5.5 MHz. The dielectric constant (εr) was varied from 1.1 × 103 to 2.18 × 103 with the amount of Nb substitution in BYTO. An impedance spectroscopic study revealed the presence of semiconducting grain and an insulating grain boundary, both of which supports the internal barrier layer mechanism and are responsible for the high dielectric constant in these materials. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.